Analisis Faktor-Faktor yang Mempengaruhi Pola Konsumsi Pangan Rumah Tangga - Siska Alfiati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Food has become a primary human need that must be fulfilled before fulfilling other living needs such as clothing, housing and education. This study aims to analyze food consumption patterns and factors that influence the food consumption patterns of households in Prabumulih City. The method of analysis is done by tabulating data, then analyzed using the calculation of energy consumption adequacy based on the PPH reference. To analyze the influencing factors carried out using multiple linear regression analysis. Sampling is done by simple random sampling method as many as 100 housewives. The results of this study indicate that the food consumption patterns of households in Prabumulih City have not reached ideal numbers. Simultaneously the income variable, the number of family members, the age of the mother, the level of maternal education significantly influence the food consumption patterns of households in Prabumulih City, while partially the income and number of families have a significant effect on household food consumption patterns in Prabumulih City. Keywords: Pattern of Food Consumption, Household.